Learner Agency, Dispositionality and the New Zealand Curriculum Key Competencies. - Jennifer Charteris (New Zealand Journal of Teachers' Work)
As more than just knowledge and skills, The New Zealand Curriculum (Ministry of Education, 2007) key competencies encompass dispositions for lifelong learning (OECD, 2005). A range of studies associate learner agency within the dispositions that are embedded in these key competencies (Carr, 2004; Hipkins, 2010; Hipkins & Boyd, 2011). Drawn from self-determination theory (OECD, 2009; Ryan & Deci, 2000), the competencies are strongly anchored in an essentialist frame-work. Interpreted this way, competencies can be likened to a virtual backpack that students carry about and draw from at will. A discursively constituted view of identity would suggest that this is not the case. Employing Davies’ (2010) conception of a subject-of-thought, where the subject is under erasure, the paper explores what agency as dispositionality can look like when it is performatively constituted in a competence-oriented curriculum (Ministry of Education, 2007). Rather being attributed static, essentialised identities, students are co-constituted in classroom discourses. The research has implications for how educators recognise moments when students agentically mobilise personal, social and discursive resources (Davies, 1990) in the classroom. This article presents an argument for a dynamic theory of agency that incorporates a rhizomatic view of learner participation and interrupts essentialist interpretations of dispositionality. It opens up possibilities for new conceptions of key competencies as performative discursive practices.